Development of Science as a Philosophical Problem - Skersytė, Jūratė (Problemos, 1977)
The article elucidates the philosophical status of the problem of the development of science relative to a differentiated concrete scientific investigation of the problem. In this connection, much consideration is given to the formulation of this problem in Marxist philosophy. The consistency of dialectical thinking requires to acknowledge the methodological nature of dialectics which alone makes it possible to substantiate theoretically its methodological function as well as the exceptionally philosophic significance of the scientific investigation of science itself. Analysis and criticism of the attempts to introduce ontological criteria into the explanation of the philosophic status of the problem of the development of science, occasionally encountered in Soviet philosophic publications, are given due attention. A logical consequence of this approach is the view which regards the development of science as a purely ontological feature of science and involves an illicit separation of the problems of philosophy from the problems of concrete scientific investigation of science. A conclusion is drawn that the philosophic sense of the problem of the development of science is conditioned by the methodological nature of philosophy itself. This problem in philosophy always has concrete historical contents and cannot be, therefore, unconditionally defined.